Cultural Construction of the Tamambaloh Apalin Dayak Community for Sustainable Forest Management - Adi, Bambang Tri Sasongko; Supriyanto, Bambang; Nailus, Fajri; Heriyanti, Lesti; Ilham Mustofa, Ihyauddin; Firdaus, dan (European Journal of Applied Sciences, 2024)
This writing explores the cultural construction of the Tamambaloh Apalin Dayak community in the context of sustainable forest management. The research methodology involves literature review, interviews with community figures, and secondary data collection. Data analysis employs a qualitative descriptive approach. In West Kalimantan (Indonesia), specifically in Kapuas Hulu District, the indigenous Tamambaloh Apalin Dayak community has a territorial area that traditionally serves as their living space. They have a strong relationship with nature as a source of life, and their environment is closely tied to economic, social, and cultural systems. They also have customary rules and institutions governing social relations among the community and their environment. The research reveals several significant findings. Firstly, the village of Sungai Uluk Palin, the residence of the Tamambaloh Apalin Dayak community, is categorized as vulnerable to the impacts of climate change. Threats from forestry and plantation concessions, forest fire disasters, and a subsistence livelihood system contribute to their high vulnerability. Secondly, this community possesses strong local wisdom in preserving and conserving the forest, making it a crucial element in sustainable forest management. This serves as an important asset for the community to overcome their vulnerability. Thirdly, the traditional land ownership system is a strength for the community to sustainably manage ancestral lands and achieve economic benefits. Fourthly, official recognition of the existence and rights of the Tamambaloh Apalin Dayak community in forest management is necessary to ensure they can optimally preserve the forest and obtain sustainable economic benefits.